2013
DOI: 10.3126/ajms.v4i4.7997
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Leprosy Patients with Clinico-Histopathological Correlation: A Hospital Based Study

Abstract: Introduction: Leprosy is a chronic granulomatous, infectious disease involving skin and peripheral nerves. It is present in various clinicopathological forms depending upon immune status of the patients. Histopathological examination of skin provides confirmatory diagnosis in suspected cases and gives indication of progression and regression of disease under treatment. Ridley and Jopling classification is used to classify leprosy. The objective of study was to identify the clinical pattern of leprosy and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…In this study, age, sex group distribution are in accordance with the epidemiology of leprosy reported in literature. 1,[13][14][15][16] The age of the patients varied from 8 to 66 years, similar to the observation by Thakkar et al 17 Maximum number of patients belonged to the age group of 31-40 years followed by 21-30. Similar pattern is observed in others studies also.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, age, sex group distribution are in accordance with the epidemiology of leprosy reported in literature. 1,[13][14][15][16] The age of the patients varied from 8 to 66 years, similar to the observation by Thakkar et al 17 Maximum number of patients belonged to the age group of 31-40 years followed by 21-30. Similar pattern is observed in others studies also.…”
Section: Discussionsupporting
confidence: 64%
“…Similar findings are noted by other studies. 5,6,10,11 Generally leprosy believed to be common in males. In the present study gender wise marginal male predominance was observed with male to female ratio of 1.33:1.…”
Section: Histopathological Pattern Of Diseasementioning
confidence: 99%
“…8 Histo-pathological examination is required when there is difficulty in diagnosing the cases clinically. 4,5,7 Thus histopathological examination is the gold standard for the accurate diagnosis of leprosy. It is also useful in classifying the cases accurately.…”
Section: Histopathological Pattern Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings are noted by other studies. 11,12,13,14,15 Generally leprosy believed to be common in males. In the present study gender wise male predominance was observed with male to female ratio of 2.14:1.…”
Section: Discussionmentioning
confidence: 99%